Sulfate Sources of Thermal Sulfate Reduction (TSR) in the Permian Changxing and Triassic Feixianguan Formations, Northeastern Sichuan Basin, China. (7th May 2019) - Li, Pingping; Zou, Huayao; Hao, Fang; Yu, Xinya
Abstract : Thermal sulfate reduction (TSR) occurred throughout the Permian Changxing (P2 c) and Triassic Feixianguan (T1 f) dolostone reservoirs in the western and eastern parts of the Kaijiang-Liangping (K-L) trough in the northeastern part of the Sichuan Basin. To determine the sulfate sources of this TSR, fourteen solid bitumen samples and eight anhydrite samples were collected from the northeastern part of the Sichuan Basin. These samples were analyzed to determine their sulfur isotopes. In addition, untreated, HNO3 -treated, and CrCl2 -treated solid bitumen samples were analyzed to determine their sulfur isotopes in order to obtain reliable δ 34 S data for the TSR solid bitumen. The results show that the HNO3 method is more effective at removing pyrite from solid bitumen than the method using CrCl2 thrice because the HNO3 -treated solid bitumen has lower sulfur contents and higher δ 34 S. The δ 34 S of the T1 f solid bitumen samples from the Puguang gas field (in the eastern part of the K-L trough, 12.0-24.0‰) is significantly lower than that of the samples from the Yuanba gas field (in the western part of the K-L trough, 24.1-34.2‰). The δ 34 S of the T1 f 1–2 anhydrite is 18.1-26.6‰, which is lower than that of the T1 f 3–4 anhydrite samples (29.9-39.6‰). The TSR sulfates from the Puguang gas field were most likely from the coeval T1 f 1–2 evaporating seawater and were enriched during the reflux-seepage dolomitization process. The TSR sulfates from the Yuanba gas field were primarily caused by the evaporation of seawater during the T1 f 4 . First, the evaporating seawater would flow vertically into the P2 c reservoirs in the adjacent area, and then, it would flow laterally into the P2 c reservoirs in the Yuanba gas field. Considering the fact that the sulfate sources of TSR and the δ 34 S values of the TSR sulfates are different in the Puguang and Yuanba gas fields, the δ 34 S of TSR solid bitumen cannot be simply used to show the extent of TSR.